The Purpose and Function of the Hadith About the Economy - La Coy; Ahmad Mohammad Tidjani (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2024)
The main purpose of the hadith about the economy is to provide clear and practical guidelines regarding economic principles in accordance with Islamic teachings. These hadiths function to explain and expand the economic concepts contained in the Qur'an, such as zakat, infaq, and social justice. Thus, the hadith contributes to the formation of an ethical, just and responsible economic attitude and behavior, in accordance with the principles that exist in Islam. The goals and functions of the hadith about the economy in Islam include several important aspects such as providing instructions on the procedures for correct and fair economic transactions, including the prohibition on usury (interest) and business practices carried out, fulfilling obligations as Muslims, namely paying zakat that aims to reduce social inequality and increase solidarity in society. Therefore the authors want to describe the goals and functions of the hadith about the economy. This research is included in qualitative research based on literature study. The data source in this study analyzes the work, books, and journals relating to the goals and functions of the hadith about the economy. The results of the study explained that, the function and purpose of the hadith about the economy can provide us knowledge so that we can prevent us from usury in the economy, knowing the principle of justice in the economy, even knowing our obligations as Muslims to issue zakat.